FREQUENCY OF LEUKOPLAKIA OF THE BLADDER AND THE ROLE OF SURGICAL TREATMENT : AN ANALYSIS OF A SIX-YEAR PERIOD - Markovski, Darko; Grozdanovski, Krsto; Ivcev, Jovan; Izairi, Armend (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Bladder leukoplakia, or squamous keratinizing metaplasia (SKM), is a rare disease in which the normal transitional epithelium is transformed into a squamous epithelium over which there is a layer of keratin. In most patients, typical non-specific symptoms of the lower urinary tract are expressed. Worldwide the representation of leukoplakia of the bladder is 1:10 000 cases. Surgical treatment is currently the gold standard in leukoplakia therapy. The goals of the study are to determine the prevalence of bladder leukoplakia, as well as the impact of surgical treatment of leukoplakia on the improvement of lower urinary tract symptoms. We analyze a series of 2,665 patients diagnosed with cystitis, out of a total of 70,620 patients from the entire territory of the Republic of N. Macedonia, who were examined and treated in the urology department at the GOB "8th of September " - Skopje, for the period from 01.01.2018 to 01.06.2024. Out of 70 620 patients, 2665 patients (3.77%) were diagnosed with cystitis, of which 1768 (66.4%) were female. The IPSS (international prostate symptom score) questionnaire showed a postoperative improvement of 65.4%. Leukoplakia of the bladder is a rare urological disease, which is exclusive to the female sex. the postoperative result of the IPSS score questionnaire showed a significant improvement in symptoms. Keywords: bladder leukoplakia, lower urinary tract symptoms, IPSS score